An Analysis Of Teachers' Perceptions And Practices In Promoting Inclusive And Accessible Library Spaces In Primary Schools In Iwo Local Government Area, Osun State - Baniyaminu Opeyemi Hamzat; Nasimot Opeyemi Oyewumi; Moses Dele Amosun; Khoula Daoudi (Journal of Early Childhood Development and Education, 2025)
Background of study: School libraries are essential for fostering literacy, academic achievement, and social-emotional development by offering equitable access to diverse learning resources. However, in many primary schools, particularly in Iwo Local Government Area, Osun State, Nigeria, these spaces often lack inclusive features. Inadequate infrastructure, limited assistive technologies, and insufficient teacher training hinder the ability of school libraries to meet the needs of all learners, especially those with disabilities. Aims and scope of paper: This study explores primary school teachers’ perceptions and practices related to promoting inclusive and accessible library environments. It aims to identify current strategies, challenges, and areas needing improvement in making library spaces supportive of students with diverse learning needs. Methods: A descriptive survey design was employed. A total of 150 teachers were selected through stratified random sampling across various schools. Data were gathered using structured questionnaires, validated for reliability (Cronbach’s Alpha = 0.75), and analyzed using descriptive statistics, including mean and standard deviation. Result: The findings show that while teachers acknowledge the value of inclusive library spaces, practical implementation remains limited. Some teachers modify materials and create welcoming environments, but gaps persist in training, resource availability, physical accessibility, and collaboration with special education personnel. Conclusion: To improve inclusivity in school libraries, there is a pressing need for targeted training, improved funding, adaptive technologies, and inter-professional collaboration. These efforts will help create equitable learning environments, ensuring that all students, regardless of ability, have access to supportive and inclusive educational resources.